Factors in Developing Creative Industry - maskarto lucky nara rosmadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study aims to find out and analyze factors to support the development of creative industries. The research method used is a qualitative method with a descriptive approach. From the results of research conducted to get creative results because it is supported by highly reliable and high-quality human resources. The constraints used in developing the creative industry are snacks that are used to increase production and also from the banking sector.